One foot in Heaven : narratives on gender and Islam in Darfur, West-Sudan - Willemse, Karin, 1962- (Women and Gender: The Middle East and the Islamic World, 2007)
This book is based on extensive anthropological field-research in Kebkabiya, a town in Darfur, West-Sudan(1990-1995), when the Islamist government of Sudan had just come to power. The title of the book is a conflation of two main government perspectives on the role of women. These proved to be decisive for the ways in which two classes of working women - low-class market women and highly esteemed female teachers- negotiated their identities within the Islamist moral discourse on gender. The book focuses on the biographic narratives of one woman from each class, which are analysed as part of the multi-layered context in which the woman spoke and acted - and of which the author also formed part. Finally, the author reflects on the war in Darfur as part of a process of identities-in-construction.